The Role of Islamic Ethical Consideration in Shaping Artificial Intelligence Usage Behavior in Higher Education - Satrio Tegar Sadewo; Abdul Aziz Baihaqi; Aditya Kumala Dewi (UIN Sunan Kalijaga Yogyakarta, 2026)
Purpose—This study aims to examine the effects of perceived usefulness, perceived ease of use, and Islamic Ethical Consideration on ChatGPT usage behavior among Muslim university students in Indonesia. Design/methodology/approach—A quantitative survey was conducted with 259 respondents and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test both direct and indirect relationships within an extended Technology Acceptance Model. Findings—The findings indicate that perceived usefulness significantly increases usage behavior (β = 0.241, p < 0.001). Perceived ease of use does not directly influence usage behavior (β = 0.065, p = 0.180) but shows a significant indirect effect through perceived usefulness (β = 0.119, p < 0.001). Islamic Ethical Consideration has a significant negative effect on usage behavior (β = −0.176, p = 0.006). Research implication/limitation—This study is limited by its cross-sectional design and sample concentration, and it implies the need for ethically grounded AI guidance in higher education and broader future research. Theoretical Contribution/Originality—This study extends TAM by showing that ChatGPT usage among Muslim students is shaped not only by functional perceptions but also by Islamic ethical considerations.